2015
DOI: 10.1016/j.ajpath.2015.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Astrocyte Activation via Stat3 Signaling Determines the Balance of Oligodendrocyte versus Schwann Cell Remyelination

Abstract: Remyelination within the central nervous system (CNS) most often is the result of oligodendrocyte progenitor cells differentiating into myelin-forming oligodendrocytes. In some cases, however, Schwann cells, the peripheral nervous system myelinating glia, are found remyelinating demyelinated regions of the CNS. The reason for this peripheral type of remyelination in the CNS and what governs it is unknown. Here, we used a conditional astrocytic phosphorylated signal transducer and activator of transcription 3 k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
42
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 40 publications
2
42
0
Order By: Relevance
“…These cells indeed express protein zero (P0), a sensitive and specific marker of Schwann cells (2). Moreover, analysis by electron microscopy demonstrated that they have the typical morphology of myelinating Schwann cells (1)(2)(3)(4). These ultrastructural findings indicate that the expression of P0 by part of the remyelinating cells is not merely ectopic, but that these cells may correspond to authentic Schwann cells.…”
mentioning
confidence: 74%
See 2 more Smart Citations
“…These cells indeed express protein zero (P0), a sensitive and specific marker of Schwann cells (2). Moreover, analysis by electron microscopy demonstrated that they have the typical morphology of myelinating Schwann cells (1)(2)(3)(4). These ultrastructural findings indicate that the expression of P0 by part of the remyelinating cells is not merely ectopic, but that these cells may correspond to authentic Schwann cells.…”
mentioning
confidence: 74%
“…Thus, within a demyelinated lesion, oligodendrocyte remyelination occurs in regions where astrocytes are present, whereas Schwann cell remyelination preferentially occurs in the absence of astrocytes (7,9,10). Moreover, reducing astrocyte activation by a conditional genetic deletion promoted Schwann cell remyelination (1).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, no major brain defects were identified when Stat3 is conditionally deleted in neurons and glia using the Nestin promoter (Gao et al, 2004). Similarly, mice with astrocyte specific Stat3 deletion exhibited normal CNS development (Herrmann et al, 2008; Monteiro de Castro et al, 2015), but had less astrocyte activation after LPC-induced focal demyelination of spinal cord white matter and subsequently diminished remyelination by oligodendrocytes (Monteiro de Castro et al, 2015), which also suggests that successful remyelination by oligodendrocytes requires factors produced by astrocytes in a Stat3-dependent manner in the injury model. As Olig1 mediated Cre recombination selectively targets OL lineage cells, our current study reveals that Stat3 signaling in OL lineage cells, while dispensable for myelination during development, is critical for myelin repair processes after focal demyelinating injury.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, this lack of OPC maturation into OLs and differentiation of OPCs into astrocytes occurred in areas where repair is expected to occur at sites of intact axons adjacent to the infarct. Schwann cell remyelination has been seen in the CNS especially in situations where there is astrocyte loss but preservation of demyelinated axons (21,22). We stained for a marker of Schwann cell peripheral myelination, periaxin (23), in control and poststroke brains.…”
Section: Resultsmentioning
confidence: 99%